2018
DOI: 10.1080/13803395.2018.1550192
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behavior among adolescents: The role of decision-making, problems from cannabis use and externalizing disorder symptoms

Abstract: Previous research has demonstrated that externalizing symptoms, cannabis use problems, and poor decision-making abilities are each independently related to risky sexual behavior (RSB). However, few studies have examined the joint effect of these factors on RSB among a sample of adolescents. The current study addresses this gap in the literature by examining how externalizing disorder symptoms, cannabis use, and decision-making abilities interact to predict RSB among a sample of adolescents (n = 204; mean age =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In line with our first hypothesis, externalizing symptoms were most strongly associated with RSB. This result concurs with previous studies that have investigated the association between RSB and externalizing symptoms [ 3 , 19 21 , 23 25 ]. According to the Problem-Behaviour Theory the association between externalizing symptoms and RSB relates to multiple psychosocial risks including personality characteristics (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our first hypothesis, externalizing symptoms were most strongly associated with RSB. This result concurs with previous studies that have investigated the association between RSB and externalizing symptoms [ 3 , 19 21 , 23 25 ]. According to the Problem-Behaviour Theory the association between externalizing symptoms and RSB relates to multiple psychosocial risks including personality characteristics (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have mostly stressed the importance of externalizing symptoms for RSB during adolescence, with reports of a broader range of externalizing symptoms being associated with more RSBs, including the number of sexual partners, frequency of using protection and frequency of drug and alcohol use during sex [ 19 ]. In addition, delinquency in early adolescence has been associated with having multiple sexual partners, an STI diagnosis [ 20 ] and with early sexual initiation [ 21 ], which itself is associated with future RSB [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is theorized that DM processes aimed at avoiding loss is compromised among those with substance use disorders (Cousijn et al, 2013). Moreover, using the same cohort of adolescents as the present study, Ross et al (2019) found cross-sectional associations between CU-related problems and poorer performance on the Cups-Loss trials but not with poorer performance on the Cups-Gain trials. Differential examination of DM during gain versus loss trials may provide a more nuanced understanding of whether (and how) risky DM predicts escalation in CU across adolescence.…”
supporting
confidence: 48%
“…Both aim to help adolescents consider the consequences of their choices (especially with delinquent peers) before making decisions (1,36,57,61,88,89,95). These were followed by allowing adolescents to bear the consequences of poor decisions without bailing them out (5,41,60,101,102). Three studies (59, 61, 68) included family cohesion measures, i.e., strength of the emotional bonds between family members' mutual support under distressed environments and situations (103).…”
Section: Discussionmentioning
confidence: 99%